Municipal solid waste shear strength parameters defined through laboratorial and in situ tests - Cristina Gomes (2013)
This paper presents the parameters of municipal solid waste shear strength determined in the laboratory (triaxial tests) and by in situ tests: standard penetration tests (SPT) and cone penetration tests (CPT). The results analyzed here are part of a study carried out on the Santo Tirso landfill (north of Portugal) between 2001 and 2007. The influence of the strain levels, waste composition, and waste age on the shear strength parameters is presented, as well as an attempt to establish some correlations between the SPT and CPT tests and to estimate municipal solid waste (MSW) friction angles from the SPT tests. The results indicate that the aging of the waste, which is characterized by a decrease in fibrous and organic materials and an increase in inert materials and fine fraction, leads to an increase in frictional resistance and to a decrease in cohesion. The results of the SPT and CPT tests indicate higher penetration resistance in older and deeper waste. Estimating the frictional resistance from the SPT test seems to obey an empirical relationship expressed by a power function, which depends on the strain level.